2016
DOI: 10.1055/s-0042-101164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipoic Acid on Serum Paraoxonase-1 and Paraoxonase-3 Protein Levels and Activities in Diabetic Rats

Abstract: The aim of the present study was to investigate the effect of streptozotocin-induced diabetes mellitus and lipoic acid treatment on serum paraoxonase-1 and paraoxonase-3 protein levels and paraoxonase, arylesterase and lactonase activities.36 rats were equally and randomly divided into 4 groups as control, lipoic acid, diabetes and diabetes+lipoic acid. To induce diabetes, a single dose of streptozotocin (40 mg/kg) was injected intraperitoneally to diabetes and diabetes+lipoic acid groups. Lipoic acid (10 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…In our study 200 μM lipoic acid caused a significant increase on both PON3 protein level and mRNA expression. This finding indicates that lipoic acid induces PON3 gene expression and supports our previous study which showed that lipoic acid increases serum PON3 protein levels and the increase percent of serum PON3 protein is higher than that of serum PON1 protein in lipoic acid-treated diabetic rats (Ozgun et al 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study 200 μM lipoic acid caused a significant increase on both PON3 protein level and mRNA expression. This finding indicates that lipoic acid induces PON3 gene expression and supports our previous study which showed that lipoic acid increases serum PON3 protein levels and the increase percent of serum PON3 protein is higher than that of serum PON1 protein in lipoic acid-treated diabetic rats (Ozgun et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…In our previous study, we reported that lipoic acid prevents an increase in lipid peroxidation of the liver; therefore it has protective effects against to hepatic ischemia/reperfusion injury in rats (Ozgun et al 2014). In another study, we also reported that lipoic acid treatment causes an increase in serum PON1 and PON3 protein levels and enzyme activities in diabetic rats (Ozgun et al 2016). Despite several previous reports on the effects of lipoic acid on paraoxonase enzymes protein and activity, no study has ever been performed to specifically examine the effect of lipoic acid on PON1 and PON3 mRNA expression.…”
Section: Introductionmentioning
confidence: 82%
“…LA has direct and indirect antioxidant properties and has been proposed as a potent antioxidant for the treatment of DM and its complications (19,20). In our previous study, we showed that LA increased serum PON activities and decreased serum lipid peroxidation in experimental diabetes (18).…”
Section: Introductionmentioning
confidence: 82%
“…PON enzymes have different activities toward different substrates, but their primary activity is lactanose activity (14). It has been shown that serum PON enzyme activities are decreased in both myocardial infarction (15,16) and diabetes (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…PON1 arylesterase activity was found to be an independent predictor of myeloperoxidase levels in general or when studied separately in the subgroups with or without cardiovascular complications [17]. In addition it has been shown that in experimental animals diabetes causes a significant decrease whereas lipoic acid treatment caused a significant increase in serum PON1 levels [18]. PON1 levels were not different between patients with acromegaly and controls despite elevated oxidative stress and increased prolidase activity in acromegaly patients [19].…”
mentioning
confidence: 96%